ISLAMIC LAW AND BUSINESS ETHICS PERSPECTIVES TOWARDS BURNING FOREST AS METHOD TO LAND CLEARING - Arrisman Arrisman (AHKAM : Jurnal Ilmu Syariah, 2018)
Burning forest as one method to clear land has made many losses not only to the welfare of the people in Indonesia, but also to the environment. However, studies examined these issues from the perspectives of the government’s laws, the Islamic Law and the business ethics have been limited. For that reason, this study aims at discussing the perspectives of the government’s law, the Islamic law and business ethics toward forest burning as a method to land clearing. The method used is by undertaking doctrinal research. The sources of the data were from primary and secondary legal materials. The study found that there have been government’s laws and regulations to ban forest burning activity. These laws include the Law No. 32 of 2009 on the Protection and Environmental Management, the Law No. 41 of 1999 on Forestry, the Law No. 18 Year 2013 on the Prevention and Eradication of forest destruction, and the Law No. 39 of 2014 on Plantations to name only four laws. The Islamic law has given guidance to human beings in managing the natural resources. These guidance have been highlighted in Surah Albaqarah 2:30 and Surah Al-Ghashiyah 88:17. Also, it is argued that compliance with the existence of business ethics will be a strong reason for the establishment of a close relationship between the company and the community. The public will be very pleased with the company in running its operations in accordance with business ethics. For this reason, it is suggested that the business plantations and other corporations  should comply with the business ethics. This aims simply to maintain harmony between business activities and the nature. So that, the corporations will be able to sustain their business activities, while at the same time the people will have certainty to have healthy environment.